Systematic selection of material for an amperometric glucose biosensor - Abd. Aziz, Azila (Penerbit UTM Press, 2009)
The internal selective membrane for an amperometric glucose biosensor was selected quantitatively based on its transport properties. A rotating disk electrode was used to obtain the permeability of acetaminophen, a common interferent for peroxide-based glucose biosensor, and hydrogen peroxide through cross-linked poly(vinyl alcohol) (PVA). All diffusion experiments were performed using a gold rotating electrode as platinum electrode exhibited slow electron transfer on its surface during the oxidation of acetaminophen, thus rendering it ineffective for this work. Selectivity of crosslinked PVA to peroxide was based on the permeability of peroxide compared to that acetaminophen. As hydrogen peroxide is small, its permeability was only affected when the mesh size of cross-linked PVA was significantly reduced. The permeability of the bigger acetaminophen, on the other hand, was linearly proportional to the mesh size of the cross-linked PVA. Cross-linked PVA membrane was found to display marginal selectivity towards peroxide.